Executive functions in kindergarteners with high levels of disruptive behaviours. (21st July 2015) - Monette, Sébastien; Bigras, Marc; Guay, Marie‐Claude
<x xml:space="preserve">Abstract</x> Executive function (EF) deficits have yet to be demonstrated convincingly in children with disruptive behaviour disorders (DBD), as only a few studies have reported these. The presence of EF weaknesses in children with DBD has often been contested on account of the high comorbidity between DBD and attention‐deficit/hyperactivity disorder (ADHD) and of methodological shortcomings regarding EF measures. Against this background, the link between EF and disruptive behaviours in kindergarteners was investigated using a carefully selected battery of EF measures. Three groups of kindergarteners were compared: (1) a group combining high levels of disruptive behaviours and ADHD symptoms (COMB); (2) a group presenting high levels of disruptive/aggressive behaviours and low levels of ADHD symptoms (AGG); and (3) a normative group (NOR). Children in the COMB and AGG groups presented weaker inhibition capacities compared with normative peers. Also, only the COMB group showed weaker working memory capacities compared with the NOR group. Results support the idea that preschool children with DBD have weaker inhibition capacities and that this weakness could be common to both ADHD and DBD.